Study of the provisions and their impact on cognitive skills in preschool. (2022)
This article is the result of an investigation and the main objective was to analyze the influence of cognitive dispositions on the learning process of (pre-school) grade students at the Nueva Granada School in the city of Tunja. For this case, didactic strategies were implemented in the area of pre-mathematics and pre-writing, thus favoring the interaction of students, both with their peers and in the development of the proposed activities. This study had a qualitative research method and action research methodology, using the observation process and interviews to collect data. The conclusions show that encouraging cognitive dispositions in students is essential and the different factors that influence them must be taken into account in order to generate new ways of thinking and favor the emergence of new intellects through meaningful learning.